Forms out of place and always well placed. Cordoba, Kronfuss and the Provincial Museum (1911 - 1916) - Agüero, Ana Clarisa (Centro de Investigaciones de la Facultad de Filosofía y Humanidades, 2007)
Between 1911 and 1916 a number of official actions directed to a culturally biased reformulation of the “Museo Politécnico Provincial de Córdoba” took place. As they show an inusual continuity and involve all museum aspects: as an institutuion, in his bulding an collections, they may be considered parts of a sole event which can be studied on a microscale analysis of it different aspects. Due to editorial reasons I will chose a significant portion of the total event, in order to show the way in which spatial and formal imagination is related to collection policies and typological changes of the institution. Therefore, this article limits itself to consider the singular building proceedings developed on the Museum, and also his architect’s trajectory showing the degree in which this local reformulation is in dialog with that of other places and traditions.As there are few antecedents and multiple common places in regard to both questions I shall try on one hand to reconstruct and reasonably explain bulding proceedings, and on the other to link succesive proyects (one of colonial inspiration, and classical one the other) to the encyclopedia and the shifting position that made possible J. Kronfus to imagine them.